+0  
 
0
32
3
avatar+170 

Let $f(x) = 12x^9 + x$. Find $f(3) + f(-3)$.

 Feb 15, 2021
 #1
avatar+29193 
+2

Hey QM....this is VERY similar to your other question which  I showed you how to answer....you should be able to do this one....try it! cheeky

https://web2.0calc.com/questions/help-ep

 Feb 15, 2021
 #2
avatar+79 
+2

This is very easy...

We have $f(3) = 12(3)^9 + 3$ and $f(-3) = 12(-3)^9 + (-3)$. Adding, this is $12(3)^9 + 3 + 12(-3)^9 + (-3)$. Since $(-1)^9 = -1$, this simplifies as $12(3)^9 + 3 - 12(3)^9 - 3 = \boxed{0}$.

 Feb 15, 2021
 #3
avatar+170 
0

Thanks though I already solved it...

QuestionMachine  Feb 15, 2021

42 Online Users

avatar
avatar